A Comparative Analysis of ARCH/GARCH and Decomposition-ARIMA Models for Gold Price Forecasting in Indonesia - Hutajulu, Ronald; Agustina, Neli (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2024)
Gold is considered a low-risk investment, serving as a hedge asset and haven against inflation and economic shocks. While gold prices exhibit an increasing trend in the long term, they are subject to short-term fluctuations. Accurate gold price prediction is crucial for investors to maximize returns. This research aims to identify the most suitable method for forecasting gold prices in Indonesia, comparing the decomposition-ARIMA and ARCH-GARCH models. The findings reveal that the decomposition-ARIMA(2,1,2) method surpasses the GARCH(1,0) model in accuracy. The forecasting results indicate an upward trend in gold prices, with an average IDR of 1,209,214.11. This study demonstrates the superior accuracy of the decomposition-ARIMA method for gold price forecasting in Indonesia, offering valuable insights for investors seeking to optimize their investment strategies.Keywords: ARCH-GARCH model; forecasting; gold; volatility. AbstrakEmas dianggap sebagai investasi berisiko rendah, berfungsi sebagai aset hedge dan safe haven yang aman terhadap inflasi dan guncangan ekonomi. Meskipun harga emas menunjukkan tren peningkatan dalam jangka panjang, harga emas juga dapat mengalami fluktuasi dalam jangka pendek. Prediksi harga emas yang akurat sangat penting bagi investor untuk memaksimalkan keuntungan. Penelitian ini bertujuan untuk mengidentifikasi metode yang paling sesuai untuk meramalkan harga emas di Indonesia, dengan membandingkan model dekomposisi-ARIMA dan model ARCH-GARCH. Temuan menunjukkan bahwa metode dekomposisi-ARIMA(2,1,2) melampaui akurasi model GARCH(1,0). Hasil peramalan menunjukkan adanya tren kenaikan harga emas dengan harga rata-rata Rp 1.209.214,11. Kontribusi studi ini terletak pada demonstrasi akurasi metode dekomposisi-ARIMA yang unggul dalam peramalan harga emas di Indonesia, sehingga menawarkan wawasan berharga bagi investor yang ingin mengoptimalkan strategi investasinya. Kata Kunci: model ARCH-GARCH; prediksi; emas; volatilitas. 2020MSC: 62M10.